Promoting Student Learning in Criminal Justice, STEM, and Forensic Science: Aggie Sleuth Initiative (AggieSI)-Guided Inquiry Learning Experience. Issue 2 (3rd April 2017) - Fakayode, Sayo O.; Mayes, James P.; Kanipes, Margaret I.; Johnson, David; Cuthbertson, Ernest L.
Abstract : This study reported the first interdisciplinary Aggie Sleuth Initiative (AggieSI) conducted between the Departments of Political Science and Criminal Justice, Sociology and Social Work and Chemistry in order to interest underrepresented minority students in the field of forensic science at North Carolina Agricultural and Technical State University (NCA&T). The AggieSI project involved a "simulated crime scene" and a "hypothetical narrative" that provided the "simulated circumstances" for the AggieSI exercise. The students worked in groups on their AggieSI projects in a guided inquiry laboratory experiment format. The students found their AggieSI project motivating, promoting the students' critical thinking, problem-solving and teamwork skills with students from other departments. This project also promoted mutually beneficial collaborations and partnerships between NCA&T and the local Police Department to further promote forensic studies and to ensure justice and public safety in our community.